2014
DOI: 10.1155/2014/483574
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Methanogen Diversity in Horse and Pony by UsingmcrAGene and Archaeal 16S rRNA Gene Clone Libraries

Abstract: Comparative analysis of methanogen compositions in the feces of horse and pony was carried out by constructing the α-subunit of methyl coenzyme-M reductase (mcrA) gene and 16S ribosomal RNA gene (16S rRNA) clone libraries. The mcrA clone library analysis indicated that Methanomicrobiales was predominant in both horse and pony. Furthermore, most of the clones of the 16S rRNA gene library showed that Methanomicrobiales was also predominant in horse and pony, but the LIBSHUFF analysis showed that the horse and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
4
14
0
Order By: Relevance
“…Particularly in ruminants, the role of the Archaeal methanogens in the digestion of fibre has been well documented ( St-Pierre et al, 2015 ). In equids, little is known of the functional diversity of methanogens; however, consistent with our findings, a recent study reported Methanomicrobiales as being predominant in the horse gut ( Lwin and Matsui, 2014 ). The underlying mechanisms by which GI helminths may be promoting a reduction in populations of methanogens are unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly in ruminants, the role of the Archaeal methanogens in the digestion of fibre has been well documented ( St-Pierre et al, 2015 ). In equids, little is known of the functional diversity of methanogens; however, consistent with our findings, a recent study reported Methanomicrobiales as being predominant in the horse gut ( Lwin and Matsui, 2014 ). The underlying mechanisms by which GI helminths may be promoting a reduction in populations of methanogens are unclear.…”
Section: Discussionsupporting
confidence: 91%
“…Recent data have reported different genera in the faecal ecosystem of the horse (Methanocorpusculum, Methanobrevibacter, Methanosphaera, Methanobacterium, Sulfolobus and Methanosarcina;Fernandes et al 2014;Lwin and Matsui 2014). The few studies focused on different regions of the horse GIT have shown that archaeal diversity may differ between faeces and colon, and, as also is the case for other species, faeces as the representatives of equine gut microbiome should be accepted with caution (Fliegerova et al 2016).…”
Section: (F) Horsesmentioning
confidence: 99%
“…For instance, from studies conducted in India, 94.4% of 16S rRNA gene sequences identified in the rumen of Murrah buffaloes were closely related to Methanomicrobium mobile ( Chaudhary and Sirohi, 2009 ), and abundances of 97.1 and 72.3% of the same methanogen group were reported in Surti buffaloes ( Singh et al, 2011 , 2013 ). Furthermore, archaea belonging to the order Methanomicrobiales were predominant in the GIT of Japanese local ponies and thoroughbred horses ( Lwin and Matsui, 2014 ). It remains to be determined why these methanogens were so prevalent in these particular conditions while they are usually detected at a much lower frequency.…”
Section: Prevalent Methanogens In the Git Communities Of Herbivoresmentioning
confidence: 99%